2020
DOI: 10.1186/s12916-020-01541-w
|View full text |Cite
|
Sign up to set email alerts
|

Long-term evaluation of the rise in legal age-of-sale of cigarettes from 16 to 18 in England: a trend analysis

Abstract: Objective: To assess the long-term impact of the increase in age-of-sale of cigarettes from 16 to 18 in England in October 2007. Methods: Data were collected between November 2006 and September 2018 on 252,601 participants taking part in a nationally representative survey of adults aged 16+ in England, the Smoking Toolkit Study (STS). We assessed the impact of the introduction of the increase in age-of-sale on prevalence of ever smoking, current smoking, and quit attempts, among 16-17 year olds compared with 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…Increasing the age of sale of cigarettes is one strategy that may be effective both in reducing uptake and in narrowing inequalities in smoking. 18,19 Second, the pandemic appears to have had equity-positive impacts on smoking. Progress in reducing smoking prevalence has historically been slower for disadvantaged groups.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the age of sale of cigarettes is one strategy that may be effective both in reducing uptake and in narrowing inequalities in smoking. 18,19 Second, the pandemic appears to have had equity-positive impacts on smoking. Progress in reducing smoking prevalence has historically been slower for disadvantaged groups.…”
Section: Discussionmentioning
confidence: 99%
“…This should be considered when taking into account the cost‐effectiveness of any increase in the age of sale, as it may reflect a group which is already highly responsive. Some of this decline may be a consequence of a longer‐term reduction in uptake of smoking following the increase in legal age of sale to 18 in 2007 [15].…”
Section: Discussionmentioning
confidence: 99%
“…In relation to the last of these, studies have demonstrated the long‐ and short‐term efficacy of the increase in the legal age of sale of cigarettes in England from 16 to 18 years on 1 October 2007. There was a greater immediate fall in smoking prevalence in 16–17‐year‐olds following the increase in age of sale than in older age groups and a greater long‐term decline in ever smoking among those aged 16–17 compared with those aged 18–24 [12–15].…”
Section: Introductionmentioning
confidence: 99%
“…There is good evidence that raising the MLSA to 18 is associated with reduced smoking rates in the target population in England [3][4][5] and reduced commercial tobacco purchases in Finland, [6] although a study on raised European MLSAs did not find an association with smoking prevalence. [7] Given the evidence base for MLSAs, and the uniquely harmful properties of tobacco, there has been renewed global interest in increasing MLSAs beyond 18.…”
Section: Introductionmentioning
confidence: 99%